2010
DOI: 10.1095/biolreprod.109.081679
|View full text |Cite
|
Sign up to set email alerts
|

USP8, a Regulator of Endosomal Sorting, Is Involved in Mouse Acrosome Biogenesis Through Interaction with the Spermatid ESCRT-0 Complex and Microtubules1

Abstract: Ubiquitin-specific peptidase 8 (USP8) is a deubiquitinating enzyme that works as a regulator of endosomal sorting and vesicle morphology in cultured cells. Its function in vivo is, however, unknown as USP8 gene deletion leads to embryonic lethality. Previously, we have shown that USP8 is highly expressed in male germ cells. These cells develop a peculiar acidic vesicle that is indispensable for fertilization, the acrosome; USP8 might be involved in vivo in acrosomogenesis. The objective of this study was to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 49 publications
0
56
0
Order By: Relevance
“…The mechanism that controls the rapid coordinated timing of the ubiquitination-deubiquitination reaction with ESCRT binding is unclear. Isolation of the UBE4B-Hrs-STAM complex, combined with previous isolation of the Hrs-STAM-USP8 complex (54), suggested that UBE4B, USP8, Hrs, and STAM may exist in a complex on the MVB. However, after exhaustive attempts using affinity chromatography and immunoprecipitation, we were unable to isolate a four-part complex (Hrs, STAM, UBE4B, and USP8) and, instead, continually isolated either one of the three-part complexes containing either UBE4B ϩ ESCRT-0 or USP8 ϩ ESCRT-0.…”
Section: Volume 289 • Number 5 • January 31 2014mentioning
confidence: 85%
“…The mechanism that controls the rapid coordinated timing of the ubiquitination-deubiquitination reaction with ESCRT binding is unclear. Isolation of the UBE4B-Hrs-STAM complex, combined with previous isolation of the Hrs-STAM-USP8 complex (54), suggested that UBE4B, USP8, Hrs, and STAM may exist in a complex on the MVB. However, after exhaustive attempts using affinity chromatography and immunoprecipitation, we were unable to isolate a four-part complex (Hrs, STAM, UBE4B, and USP8) and, instead, continually isolated either one of the three-part complexes containing either UBE4B ϩ ESCRT-0 or USP8 ϩ ESCRT-0.…”
Section: Volume 289 • Number 5 • January 31 2014mentioning
confidence: 85%
“…Although the precise trafficking pattern of acrosomal-resident proteins during acrosomogenesis has not been clearly defined, recent evidence suggests contributions from the early endosomal/lysosomal system [37]. A study showed that ESCRT-0 protein in spermatids was shown to be dispersed throughout the cytoplasm in a punctate pattern that colocalized with early endosome antigen 1 during the Golgi phase but localized at the acrosome in elongating spermatids, suggesting the involvement of endosomes in acrosome biogenesis [38].…”
mentioning
confidence: 99%
“…This scaffold structure was shown to contain self-aggregates of Pmel protein in an amyloid structure providing the first evidence in mammals of an amyloid carrying out a biological function (57). Our studies examining the relationship of the sperm AM to LRO revealed the highest overlap of the sperm AM with proteins present in melanosomes suggesting that the sperm AM may be structurally and functionally similar to this LRO and may in fact represent a novel LRO as proposed by (55). Further investigation of our AM proteome showed the presence of several amyloidogenic proteins including the cystatin CRES, which we have previously shown forms amyloid in vitro and in vivo within the epididymal lumen (59,60), as well as the related CRES subgroup members CRES2 and cystatin T (66, 67), cystatin C, PMEL, SOD, and several lysozyme family members.…”
Section: Isolation Of Am From Caput and Cauda Epididymal Spermatozoa-mentioning
confidence: 55%
“…Also within secretory granules, proteins are known to be compartmentalized and the acrosome reaction has been compared with the secretion process that occurs from secretory granules. Because cumulative studies do not strictly support the acrosome as being solely Golgi-derived or lysosomal in origin, (55) proposed the acrosome as a novel LRO, which are membrane-bound cytoplasmic organelles including melanosomes, endosomes, and synaptosomes that are restricted to specific cell types and that carry out functions unrelated to degradation. LROs use both the synthetic (derived from Golgi) as well as retrograde (endocytic) transport pathways during their biogenesis as seems to also occur during acrosome formation (52).…”
Section: Resultsmentioning
confidence: 99%